Evaluation of soil fertility index in organic, semi-organic, and conventional rice field management systems - Suntoro, Suntoro (2024)
Rice farming in Madiun Regency implements three different management systems, that is organic, semi-organic, and conventional. The different implementation of these rice field management systems impacts soil fertility index and rice productivity. This purpose of this research was to know the effect of rice field management systems on soil fertility index and rice productivity in the Madiun Regency. The research uses an explorative descriptive qualitative method with a survey approach. Soil samples were taken using a random sampling method and 3 types of soil management systems (conventional, semi-organic and organic), and rice production samples were taken using an estimation method. The research results show that the soil fertility index ranges from 0.78 to 0.82, which is high. The highest soil fertility index is in the semi-organic management system and the lowest is in the organic management. The management system of semi-organic gave a response to the highest rice production of 6.89 tons/ha. Management system of semi-organic is a better management for increasing and maintaining soil fertility and crop production than conventional or organic. Farming activities results show that organic management systems increase the highest income, increasing 115.58% and 53.30% in semi-organic compared to conventional. The rice field management system has the effect of increasing the worm population density with the highest in the organic system, namely 4.19 individuals m-2. The Pontoscolex worm type dominates the three management systems. There is a correlation between organic matter content and earthworms.